The Response Forms of Students toward the Integration of Minangkabau Local Wisdom Values - Fikri, Hasnul; Syofiani, Syofiani; Isnanda , Romi; Morelent, Yetty (Indonesian Research Journal in Education |IRJE|, 2023)
This research aimed to describe the integration of kato nan ampek into the learning process for religion, citizenship, and indonesian language courses at one private. This research collected data through the forms of student responses to lecturers’ verbal communication which were collected via online questionnaires. The research subjects were lecturers and students who took these three courses. The questionnaire was analyzed using by using simple statistical techniques. The results showed that the lecturer had integrated kato nan ampek into learning. Students were placed in a position that was close or equal to the lecturer, not at a distance or lower, by addressing greeting Ananda or Saudara. This message of appreciation and closeness reached students. It was also reflected in the RAL [Respondent's Achievement Level] results, which showed that responses were in good qualifications. Based on subjects, the highest average RAL was found in Religion courses, while based on learning activities, the highest RAL was in the opening aspect of learning.